Exploring How Public Health Partnerships with Community-Based Organizations (CBOs) can be Leveraged for Health Promotion and Community Health - Senila Yasmin MPH; Rayna Haque; Kaneza Kadambaya MPH; Marzia Maliha; Maha Sheikh (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
The Academic Public Health Corps (APHC) works to support local public health in Massachusetts through varying models of collaboration. In the setting of the COVID-19 pandemic, one initiative of the APHC has been to partner with community-based organizations (CBOs) to address vaccine hesitancy and improve overall community health. The purpose of this article is to share how the APHC partnered with CBOs in Massachusetts to address COVID-19 concerns within their respective communities, and present strategies to empower communities, share resources, and increase health promotion. The APHC partnered with 2 CBOs who received the Massachusetts COVID-19 Community Grants distributed by Health Resources in Action (HRiA). These CBOs include the Association of Islamic Charitable Projects Massachusetts (AICP) and the Somali Parents Advocacy Center for Education (SPACE). Culturally relevant educational and promotional materials were created and tailored toward the communities of interest within the CBOs. Additionally, in response to the community’s desire for more informational events, the APHC hosted a virtual COVID-19 Q&A panel with Muslim health care professionals that included live Arabic translation. The model of outreach that the APHC has employed illustrates an intentional way of addressing key public health issues within local communities. The success of these partnerships highlights the importance of including CBOs in conversations about public health and health equity.